Analysis of Qordhul Hasan Financial Management at The Non-Bank Islamic Financial Institutions: Evidence from Islamic Saving and Loan Cooperative - Miftahul Janah; Dwi Harmoyo; Edo Segara Gustanto (Department of Islamic Banking, 2024)
The purpose of this research is to find out the management of Qordhul Hasan and analyze it based on the management functions implemented at BMT Beringharjo. This research is field research with a qualitative and descriptive approach. Primary data were obtained from interviews with management, managers, and members of BMT Beringhgarjo, while secondary data is in the form of notes or papers from various scientific works, the internet, or publications about this research problem. Methods of data collection used observation, interviews, and documentation Assessment of the validity of the data used triangulation techniques, sources, and time Data analysis involves the processes of data collection, data reduction, statements, and concluding. The results of the study show that BMT Bringharjo has implemented Qardhul Hasan financing product management since the submission of the application to completion. BMT Bringharjo in implementing the functions of Qardhul Hasan's financing management as follows: Planning, including the source of funds targeting officers and administration. Organizing includes human resources, time scheduling, and fund allocation. Implementation includes application services, appraisal, realization, installments, billing, and settlement. Control includes monitoring borrower members based on current, substandard, doubtful, and loss categories with different handling according to the Qardhul Hasan financing category.